Literature Review: The Relationship of Anxiety Towards The Production of Breast Milk in Postpartum Mothers - Fatmawati Fatmawati; Berliana Maduratna Irawati; Hafidza Auliya (Publikasi Indonesia, 2022)
The postpartum period is a vulnerable period for postpartum mothers because there are several physiological and psychological changes after giving birth. Otherwise, the process of lactation and milk production is influenced by hormones. Postpartum mothers usually feel tired and experience psychological disorders such as anxiety about their condition and the condition of their baby. This study aims to determine the conditions that interfere with the production of breast milk in postpartum mothers. This study uses traditional literature review research methods, analyzes articles that match the inclusion criteria, and focuses on the relationship between anxiety and increased breastfeeding in postpartum mothers. Based on the results of this study, this literature review used 10 journals with inclusion criteria, eight journals showed a significant relationship between anxiety and breastfeeding in postpartum mothers. There was a decrease in oxytocin levels and duration of breastfeeding which had an impact on the rate of exclusive breastfeeding. In contrast, the other two journals did not find a significant relationship between anxiety and oxytocin levels with the breastfeeding method used. Because there are variables that are not examined.